2019
DOI: 10.1021/acs.jafc.9b01749
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive SPE Derivatization–UHPLC–MS Approach for Quantitative Profiling of Carotenoid-Derived Dialdehydes from Vegetables

Abstract: Oxidative cleavage of carotenoids leads to dialdehydes (diapocarotenoids, DIALs) in addition to the widely known apocarotenoids. DIALs are biologically active compounds that presumably impact human health and play different roles in plant development and carotenoid metabolism. However, detection of DIALs in plants is challenging due to their instability, low abundance, and poor ionization efficiency in mass spectrometry. Here, we developed a solid-phase extraction and derivatization protocol coupled with ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…This approach led to the discovery of the presumed diapocarotenoid anchorene as a novel carotenoid-derived bioactive that promotes the development of anchor roots (ANRs) (Jia et al, 2019a), a less investigated type of Arabidopsis roots, which develop from the collet region situated at the root hypocotyl junction (Lucas et al, 2011). Although it is still unclear how it is formed, anchorene (C 10 ) is a natural metabolite, as confirmed by LC-MS analysis (Jia et al, 2019a; Mi et al, 2019a), and its structure indicates that it can be produced by cleaving the (C11–C12) and (C11′–C12′) double bound from all carotenoids downstream of ζ-carotene in the carotenoid biosynthesis pathway ( Figure 5B ). In Arabidopsis , application of anchorene induces ANR formation.…”
Section: Novel Carotenoid-derived Signaling Moleculesmentioning
confidence: 97%
“…This approach led to the discovery of the presumed diapocarotenoid anchorene as a novel carotenoid-derived bioactive that promotes the development of anchor roots (ANRs) (Jia et al, 2019a), a less investigated type of Arabidopsis roots, which develop from the collet region situated at the root hypocotyl junction (Lucas et al, 2011). Although it is still unclear how it is formed, anchorene (C 10 ) is a natural metabolite, as confirmed by LC-MS analysis (Jia et al, 2019a; Mi et al, 2019a), and its structure indicates that it can be produced by cleaving the (C11–C12) and (C11′–C12′) double bound from all carotenoids downstream of ζ-carotene in the carotenoid biosynthesis pathway ( Figure 5B ). In Arabidopsis , application of anchorene induces ANR formation.…”
Section: Novel Carotenoid-derived Signaling Moleculesmentioning
confidence: 97%
“…Ion fragments appear in very low intensities, even increasing the positive collision energy (> 20eV). It has been reported that diapocarotenoids or dyaldehydes produced from the oxidative cleavage of carotenoids have a low ionization efficiency in mass spectrometry (Mi et al, 2019). In the case of BoCCD1-3 and BoCCD4-4 we found a very small peak corresponding to m/z 350 [M + 2] + and m/z 349 [M + 1] + , respectively, that was impossible to fragment (Supplementary Figure 10).…”
Section: Boccd1 and Boccd4 Enzymes Are Involved In Bixin Aldehyde Bio...mentioning
confidence: 83%
“…In all the bacterial extracts the bixin aldehyde peak (m/z 349.1) was not prominent when injected directly (Supplementary Figure 7). It is also possible that the low intensities are due to the low amount of bixin aldehyde, or its high consumption efficiency (Rubio-Moraga et al, 2008;Mi et al, 2019). Results indicate that the BoCCD1-4, BoCCD4-1, and BoCCD4-2 enzymes are capable of cleaving lycopene at 5,6/5 ,6 double bonds to produce bixin aldehyde, as BoCCD1-1 and BoCCD4-3 do.…”
Section: Boccd1 and Boccd4 Enzymes Are Involved In Bixin Aldehyde Bio...mentioning
confidence: 99%
“…Furthermore, diapocarotenoids are widely present in plants (Fiorilli et al , 2019; Jia et al , 2019a; Mi et al , 2020). Examples of in planta identified diapocarotenoids are crocetin dialdehyde (C 20 ), which is the precursor of crocin (Frusciante et al , 2014), anchorene, which is a C 10 dialdehyde that regulates anchor root formation in Arabidopsis (Jia et al , 2019), and a series of diapocarotenoids with different chain lengths, which are present in tomato fruit ( Solanum lycopersicum ; Mi et al , 2019). In this study, we show that iso‐anchorene is a further diapocarotenoid that occurs in Arabidopsis and fulfills a specific biological function in inhibiting primary root growth (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…This is due to their instability and low abundance in biological systems, which impede their detection and the elucidation of their biological function. Nevertheless, it has been shown that diapocarotenoids, like apocarotenoids, are common metabolites that occur with different chain length, stereospecificities, or structural configurations (Mi et al , 2019; Mi et al , 2020). Several plant and microbial CCDs have been shown to form diapocarotenoids in vitro (Scherzinger et al , 2006; Alder et al , 2008; Ilg et al , 2014).…”
Section: Introductionmentioning
confidence: 99%